Running mechanics during 1600 meter track runs in young adults with and without chronic ankle instability. (March 2020) - Colapietro, Mark; Fraser, John J.; Resch, Jacob E.; Hertel, Jay
Abstract: Objective: To evaluate biomechanical measures in runners with and without chronic ankle instability (CAI) using wearable sensors during two 1600 m track runs at a slow- and fast-pace. Design: Observational case-control. Setting: Field. Participants: 18 recreational runners (CAI: n = 9; Healthy: n = 9) with rearfoot strike patterns. Main outcome measures: Pronation excursion, maximum pronation velocity, peak braking g, peak impact g, contact time, cycle time, and stride length of every step of two 1600 m runs were collected using RunScribe™ sensors and binned to each 400 m lap (Lap 1 to Lap 4). Results: Significant group-by-lap interactions were identified for contact time (p = .05) during the slow-intensity run. The CAI group had greater contact time (p = 0.05) that progressively increased with distance completed. CAI group also had higher impact g than the control group throughout the slow-intensity run (p = .03). During the fast-intensity run, significant group by lap interaction was observed for pronation excursion with the CAI group exhibiting less pronation excursion than the healthy group as the run progressed ( p  = .002). Conclusions: Regardless of speed, runners with CAI demonstrated altered gait mechanics compared to healthy controls. During the higher intensity run, decreased pronation excursion was observed in the CAI group and differences became more prominent as the distance increased. Highlights: Wearable sensors identified differences in gait biomechanics of CAI individuals. First study to analyze running metrics in those with CAI in a field setting. CAI group exhibited altered running mechanics while running on an outdoor track. Decreased pronation excursion was observed in the CAI group at faster intensities. Higher impact g's and increased contact time were observed in the CAI group.